THE INFLUENCE OF GLOBALIZATION ON SOCIAL STRUCTURE AND RELIGIOUS PRACTICE IN THE CONTEXT OF THE QUR'AN - Rama Fitriani; Khoiria Linermi Siregar (STAI Sebelas April Sumedang, 2022)
Abstract This study investigates the impact of globalization on social structures and religious practices within Muslim communities, analyzed through the lens of the Qur'an. By employing a qualitative approach involving content analysis and comparative studies, the research examines relevant Qur'anic verses that address social justice, cultural adaptation, and individual freedoms. The findings reveal that globalization has reshaped the social fabric of Muslim societies, introducing both challenges and opportunities. The Qur'an provides essential guidance for navigating these changes, emphasizing the need for justice, equity, and balanced adaptation to global influences. The role of Islamic scholars and religious institutions is highlighted, particularly in issuing fatwas and offering education that integrates Islamic values with contemporary global issues. This study contributes to a deeper understanding of how Islamic teachings remain relevant in the modern, globalized world, offering a framework for addressing socio-cultural transformations without compromising core religious principles.